The relationship between governance quality and the cost of equity capital in Italian listed firms: An update - Francesca Bertoncelli; Paola Fandella; Emiliano Sironi (Journal of Risk and Financial Management, 2021)
This paper investigates the relationship between corporate governance quality and the cost of equity capital, intended as the discount rate the market applies to a firm's expected future cash flows to evaluate the current share price. Using data from the Italian listed corporations in 2018, this paper combines several attributes like board independence, board size, the existence of the internal audit, and CEO duality incorporated in a corporate governance quality index. Our results do not provide evidence of a statistically significant relationship between the corporate governance score and the firm's equity capital cost. A possible explanation is that in recent years a greater homogeneity, and a generalized increase in corporate governance quality standards, has been observed in the Italian framework with worse companies that closed the gap with those with higher performances. Hence, lower variability in the corporate governance index results in a not significant effect of a composite index on reducing the cost of equity capital.
Keywords: 330; corporate governance; cost of equity; listed corporations; quality of governance